Técnicas assintóticas para predição de cobertura radioelétrica - Daniela Naufel Schettino (2002)
This work deals with the prediction of radio-electronic coverage in urban environments through the Uniform Theory of Diffraction (UTD Uniform Theory of Diffraction). The UTD is a technique that determines the asymptotic scattered field tracking him through the paths between transmitter and receiver. These trajectories are determined by an algorithm based on the method of images to trace the diffracted and reflected rays in a 2D environment. The ray tracing can be adapted to a 3D environment, where the heights of the walls that form barriers are much larger than the heights of transmitting and receiving antennas (quasi-3D analysis). Are considered multiple reflections and diffractions in the calculation of the scattered field through the separation of trajectories into four distinct classes of rays: transmitter-receiver (TR), vector-diffraction point (TD), point-point diffraction diffraction (DD) and diffraction point-receptor (DR). The complete trajectories between transmitter and receiver containing multiple reflections and diffractions are formed by the concatenation of these different classes, allowing rays that appear several times, including in the case of distinct receptors, need not be recalculated, greatly streamlining the processing time of routine ray tracing. Finally, we present some case studies in order to illustrate the algorithm implemented and validate the results. To this end, we used as comparison for the UTD Method of Moments and cases presented in the literature. Several examples were analyzed in a 2D environment with obstacles of electrical conducting surfaces perfect. The analysis of scattered fields (electric and magnetic) for the comparative cases to the Method of Moments showed minor discrepancies. Furthermore, we examined the attenuation (in dB) for two examples quasi-3D, considering the finite conductivity surfaces, the results were compared with measurements reported in the literature. In the best result of these cases occurred in regions of maximum discrepancies environment analyzed in the order of 10dB.